Avicenna and Mixed Sciences - Ribeiro do Nascimento, Carlos Arthur (Circumscribere International Journal for the History of Science, 2008)
Some of Aristotle’s texts (Physics II,2; Posterior Analytics I, 7, 9 and 13) mention some sciences (astronomy, harmony, optics and mechanics – the last one only in Posterior Analytics) in the context of the distinction between physics and mathematics (in Physics), the impossibility of using the demonstrations of one science in another one (metabasis) and the distinction between proofs of what and why (in Posterior Analytics). These texts allowed his commentators – especially the Arabic and Latin ones – to approach the epistemic status of such sciences. The present study seeks to examine how Avicenna – or more precisely, the Latin Avicenna – dealt with this issue in Liber primum naturalium, and what he would have added to Aristotle’s text. In this regard, it is possible to point out to the addition of at least two more sciences to Aristotle’s list (science of the spheres in motion and science of weights), a formal definition of this type of sciences, implying their mixed nature (Avicenna refers to astronomy): “this science is as if it were mixed from the natural and the disciplinary [mathematics] ones. As the pure disciplinary one is abstract, in no way in matter, and this one is as if inserting the abstract one in designated [determined] matter”. It is also noteworthy a terminology that cannot be found in Aristotle’s text: “mixed science” – in the Arabic text, “participating” (mushtarak) or “compounded” (murakkab) science -, “pure and inserted science”, “abstraction”.